The impact of transformational leadership on employee performance: examining the mediating role of work motivation in organizational settings - Panjaitan, Eddy Hermawan Hasudungan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In the competitive business world, employee performance is a key factor determining organizational success, particularly in the manufacturing sector and government agencies in Indonesia. Transformational leadership is recognized as an effective leadership style in enhancing employee performance through improved work motivation. However, the relationship between transformational leadership and employee performance, with work motivation as a mediating variable, requires further investigation within these organizational contexts. This study aims to analyze the influence of transformational leadership on employee performance with work motivation as a mediating variable in large manufacturing companies and government agencies in Indonesia, such as the Ministry of Industry and State-Owned Enterprises (SOEs). A quantitative approach was used with path analysis techniques. Data were collected through questionnaires distributed to 250 employees in these sectors. The research instrument was adapted from a scale previously tested for validity and reliability. The analysis results indicate that transformational leadership has a positive and significant influence on employee performance (β = 0.45; p < 0.01). Work motivation significantly mediates this relationship, with a stronger mediation effect observed in the manufacturing sector (β mediation = 0.30; p < 0.05). These findings suggest that effective leadership not only directly impacts employee performance but also indirectly through increased work motivation. The implications of this research highlight the need for leadership development programs focused on enhancing work motivation, such as training in inspirational communication skills and employee empowerment, to boost productivity in both the manufacturing sector and government agencies.